Distribution switchgear - Stewart, Stan (London, United Kingdom Institution of Engineering and Technology, 2004)
The book reviews developments in the following fields: interruption techniques; difference between a circuit breaker and a switch; fault level calculations; symmetrical and asymmetrical fault currents; electromagnetic force; contact design; switching transients; insulation; operation mechanism; primary switchgear; cable connected secondary switchgear; overhead conductor connected secondary switchgear; high-voltage fuse-links; switchgear type test; product conformity; quality control; and service problem resolution.
Electronic reproduction.
Keywords: Electric switchgear; Electronic books